Social impact bond feasibility study AEIPS intervention: housing first - Wahn, Malou-Anne (2016)
AEIPS is a Portuguese social organization promoting the integration of people with mental health illnesses and/or substance abuse in the community through the intervention model Housing First. The philosophy of Housing First aims at lifting people out of their homelessness status by providing instant access to individualized and permanent housing as well as support services. Housing First projects from all over the world have proved very positive results in terms of residential stability and community integration of its participants. This feasibility study evaluates the suitability of using a Social Impact Bond to fund the Housing First intervention of AEIPS in Portugal.